PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS SUSUKAN 2 - Handayani, Juli (Perwira Journal of Economics & Business, 2024)
The aims of the research to determine the effect of service quality on patient satisfaction at Susukan 2 Health Center. The type of research used was a quantitative cross sectional design, with an accidental sampling technique. Data analysis was pervormed by univariate, bivariate and chi-square test. The results of the research at Susukan 2 Health Center were satisfied with the good service quality at 66,4% and the bad service quality at 41,4%. Patients who feel dissatisfied with the quality of service are good at 35,6% and the quality is not good at 58,6%. The results of statistical test using the Chi- Square test obtained value = 0,023< = 0,05 the Ho is rejected and H1 is accepted which means there is an influence between service quality on patient satisfaction at Susukan 2 Health Center.